A novel type 3 secretion system effector, YspI of Yersinia enterocolitica, induces cell paralysis by reducing total focal adhesion kinase. (14th December 2014) - LeGrand, Karen; Matsumoto, Hiroyuki; Young, Glenn M.
Summary Some of the world's most important diseases are caused by bacterial pathogens that deliver toxic effector proteins directly into eukaryotic cells using type III secretion systems. The myriad of pathological outcomes caused by these pathogens is determined, in part, by the manipulation of host cell physiology due to the specific activities of individual effectors among the unique suite each pathogen employs. YspI was found to be an effector, delivered by Yersinia enterocolitica Biovar 1B, that inhibits host cell motility. The action of YspI comes about through its specific interaction with focal adhesion kinase, FAK, which is a fulcrum of focal adhesion complexes for controlling cellular motility. The interaction was defined by a specific domain of YspI that bound to the FAK kinase domain. Further examination revealed that YspI–FAK interaction leads to a reduction of FAK steady‐state levels without altering its phosphorylation state. This collection of observations and results showed YspI displays unique functionality by targeting the key regulator of focal adhesion complexes to inhibit cellular movement.